1998
DOI: 10.1515/bchm.1998.379.11.1323
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Association between Differentiation and Induction of Galectin-1, and Inhibition of Galectin-3 by Retinoic Acid in Mouse Embryonal Carcinoma F9 Cells

Abstract: Soluble endogenous lactoside-binding lectins, galectins, have been implicated in cell adhesion, growth, differentiation, neoplastic transformation, and metastasis. Two major classes of these lectins, galectin-1 and galectin-3, are developmentally regulated. To explore the mechanisms by which the expression of the galectins is regulated and to examine their association with the differentiation processes induced by all-trans retinoic acid (RA), dibutyryl cyclic AMP (Bt2cAMP) and their combination, we used the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Previous work has provided evidence that proteins within the galectin family can be regulated by O-GlcNAcylation [17,21,22]. Few studies have examined galectins in F9 cells [40,41], where we saw no changes in Lgal3 expression in F9 cell XEN differentiation (Supplementary Materials, Figure S2); however, we observed a decrease in Lgals3 expression in terminally differentiated XEN cells compared to ES cells (Figure 3). Unlike the changes in O-GlcNAc levels, which are consistent in many previous reports [15,17,18,21], galectins appear to have context-specific changes in expression, as evident from our own studies [17,20,38].…”
Section: Discussionmentioning
confidence: 50%
“…Previous work has provided evidence that proteins within the galectin family can be regulated by O-GlcNAcylation [17,21,22]. Few studies have examined galectins in F9 cells [40,41], where we saw no changes in Lgal3 expression in F9 cell XEN differentiation (Supplementary Materials, Figure S2); however, we observed a decrease in Lgals3 expression in terminally differentiated XEN cells compared to ES cells (Figure 3). Unlike the changes in O-GlcNAc levels, which are consistent in many previous reports [15,17,18,21], galectins appear to have context-specific changes in expression, as evident from our own studies [17,20,38].…”
Section: Discussionmentioning
confidence: 50%
“…Spp2 transcripts have been detected in the yolk sac (Hou et al, 2007), while Galectin-1 (LGALS1) is a β-galactoside binding lectin protein that regulates MAPK signaling in various cellular contexts (Brandt et al, 2010; Thijssen et al, 2010). The expression of LGALS1 has not been reported in vivo in the extraembryonic endoderm, but it was previously reported to be activated after retinoic acid induced endodermal differentiation of F9 embryonal carcinoma cells (Lu et al, 1998). WAP four-disulfide core domain 1 (WFDC1, also referred as PS20) was identified as a prostate secreted protein with a putative serine protease inhibitor activity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study from our group showed that melanocytes accumulate galectin-3 with tumor progression (27). Earlier, our group has also shown that retinoic acid inhibits the expression of galectin-3 and causes differentiation in mouse embryonal carcinoma F9 cells (28).…”
Section: Discussionmentioning
confidence: 94%